The Influence of Intellectual Capital, Audit Fee, and Ownership Concentration on Enterprise Risk Management Disclosure - Alfan, Inas Maritsa; Aryati, Titik (CV. Publikasi Indonesia, 2024)
This study explores the influence of financial literacy, attitudes towards money, and financial pressures on the financial well-being of non-profit workers in Indonesia, an issue that is relevant given the high social activity but lack of attention to workers' financial well-being, especially with the majority being low-income. Using the purposive sampling method on 108 respondents from various regions in Indonesia, the study revealed that financial literacy had a significant positive influence on financial well-being, while attitudes towards money had no significant effect. Conversely, financial stress had a significant negative influence on the financial well-being of non-profit workers. These findings underline the need for enhancing financial literacy and addressing financial pressures to improve workers' financial well-being. The study contributes both theoretically and practically by offering insights into the financial behavior of non-profit workers and highlighting the importance of targeted financial education programs for this sector.